Amaliah Recitation of Ratib Al-Kubra in the Routine of Wednesday Night Remembrance Assemblies Jatiseeng Kidul Village, Ciledug District, Cirebon Regency (Study of Living Hadith) - Khumaedi Nurfatsyah Zein; Anisatun Muthi'ah; Hartati Hartati (PT Publikasiku Academic Solution, 2023)
Technological advances must have positive and negative impacts. In this modern era, humans definitely need peace from the hustle and bustle of life, to get peace, the solution is to remember and pray. One of them is reading the remembrance of Ratib al-Kubra. Ratib al-Kubra is a series of dhikr compiled by Al Habib Thoha bin Hasan bin Yahya from Ciledug, Cirebon, West Java. He was a scholar who lived in the 17th century during the Dutch colonial era. One of the assemblies that practice the ratib is the Wednesday Night Zikir Assembly of Jatiseeng Kidul Village, Ciledug District, Cirebon Regency. The formulation of the problem in this study is as follows: (1) How is the practice of reading Ratib al-Kubra of the Wednesday Night Dhikr Assembly of Jatiseeng Kidul Village, Ciledug District, Cirebon Regency? (2) What is the meaning and influence of the Ratib al-Kubra dhikr for the life of the Wednesday Night Dhikr Assembly of Jatiseeng Kidul Village, Ciledug District, Cirebon Regency?This research uses a descriptive qualitative method with a living hadith approach. The data collection techniques used were participant and non-participant observation, interviews, and documentation. In analyzing the data in this thesis using descriptive analysis using the theory of living hadith and phenomenology. The results of the study are: (1) Hadith regarding dhikr became an inspiration in the recitation of the Ratib al-Kubra dhikr of the Wednesday Night Dhikr Assembly of Jatiseeng Kidul Village, Ciledug District, Cirebon Regency, its activities which were held at the tomb of the compiler of the rat?b made the congregation more enthusiastic in its practice, because in addition to reading Ratib al-Kubra it was also accompanied by a grave pilgrimage. (2) The meaning of its recitation for the congregation has a value or essence, among which is the remembrance of Ratib al-Kubra is a remembrance that can certainly establish silaturrahim, become a medium for calming the soul and also the establishment of a spiritual connection between the ratib reader and the shahib ar-ratib.